Implementasi Teknik Penilaian Blended Learning Pada Keterampilan Pembelajaran Fiqih Masa Pandemi Covid-19 - Ahmad Khoirun Nasir (JIE (Journal of Islamic Education), 2021)
The purpose of this study was to determine the application of the skill aspect of blended learning assessment techniques in fiqh learning during the covid-19 pandemic at Madrasah Ibtidaiyah Ngabar Ponorogo. The method used in this study uses a qualitative approach. The data collection using interview and documentation techniques. The results of this study indicate that the learning concept used in Madrasah Ibtidaiyah Ngabar Ponorogo uses a combination of two learning systems, namely online and offline or blended learning. The technique for assessing the skill aspect of blended learning uses performance appraisal techniques or practices and products in fiqih learning during the covid-19 pandemic and in its implementation there are advantages and disadvantages. The conclusion of this study is that the learning of fiqh at Madrasah Ibtidaiyah Ngabar Ponorogo applies a blended learning model with techniques for assessing aspects of performance skills or practices and products that are going well even though there are shortcomings in implementation in the field during the covid-19 pandemic.